RETHINKING STAFF SUPERVISION PROCEDURES IN AN ERA OF ARTIFICIAL INTELLIGENCE FOR EFFECTIVE SECONDARY SCHOOL ADMINISTRATION IN BAYELSA STATE (Scientific Journal of Educational Management, Research and law, 2026)
Staff supervision landscape is changing in this era of artificial intelligence and only schools that are proactive can achieve effective school administration in this era. This study focused on rethinking staff supervision procedures in an era of artificial intelligence for effective secondary school administration in Bayelsa State. Three research questions and related hypotheses were answered and tested in the study. The study adopted descriptive survey design and out of a population of 207 public secondary school principals in the State, 136 principals (62 males and 74 females) were sampled for the study using simple random sampling technique. Instrument used for data gathering was questionnaire named “Rethinking Staff Supervision Procedures in an Era of Artificial Intelligence for Effective Secondary School Administration Questionnaire” (RSSPEAIESSAQ) which was face and content validated by experts with a reliability index of 0.97 using Cronbach alpha statistics. There were 136 copies of questionnaire administered out of which 129 copies (57 males and 72 females) which represented 94.9% were retrieved. The research questions raised were answered using mean and standard deviation while the hypotheses were tested at 5% significant using z-test. The result of the study indicated existing staff supervision procedures included regular classroom observation andseasonal performance evaluation.The challenges of staff supervision procedures in the era of artificial intelligence included the possibility of job displacement andlack of data privacy.Automation of staff performance evaluation and provision of relevant data for decision making were ways AI can enhance staff supervision. There was no difference in the opinion of the respondents on these issues. The study recommended the digitalization of administrative practices to make the benefits of AI fully realizable